Socio-Economic Impact Of Integrated Pest Management Field School Implementation On Coffee Farmers In Panditan Village - Muqtafiah (Jurnal Serambi Ilmu, 2022)
Integrated Pest Management Field School (IPM-FS) is an extension method thatis still being applied in Indonesia. IPM-FS is considered still relevant to beapplied in Indonesia. However, farmers still have obstacles that cause farmersnot to fully apply the knowledge obtained from the Integrated Pest Control FieldSchool. The purpose of this study was to examine and analyze the benefits andconstraints after implementing the IPM-FS in Panditan Village, LumbangDistrict. The method used is descriptive qualitative. Collecting data throughobservation, interviews, and documentation. The results showed that farmersbenefited from the Integrated Pest Management Field School (IPM-FS), namelyincreasing farmer knowledge, changing farmer perceptions and behavior, andincreasing coffee productivity. The absence of a specific price differencebetween coffee with the application of IPM and non-IPM is an obstacle forfarmers so that farmers pick coffee carelessly.